2009
DOI: 10.1002/cncy.20049
|View full text |Cite
|
Sign up to set email alerts
|

Cytology of endobronchial ultrasound‐guided transbronchial needle aspiration

Abstract: BACKGROUND:Endobronchial ultrasound (EBUS) is a relatively new modality that can be used to guide transbronchial needle aspiration (TBNA) of mediastinal and hilar lymph nodes and peripheral lung lesions. Few studies have investigated the cytological profile of EBUS‐TBNA specimens. In this study, we have reviewed the cytological profile of 135 consecutive cases, including 71 lymph node cases, 4 lung cases, and 60 cases of both lymph node and lung sampling. Our study contains the largest number of cases in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 30 publications
7
103
0
Order By: Relevance
“…One group of authors reported that, of 131 cases of mediastinal lymph node sampling performed at the Johns Hopkins Hospital, 7 (5.3%) had samples that were considered inappropriate. (9) In the present study, the rate of inappropriate samples was 25%, which is similar to the rates reported in the literature for initial experiences. Contributing to that is the fact that the biopsies involved hilar lymph node stations, which had a higher rate of "inappropriate" samples when compared with the biopsies involving the subcarinal station, which is more easily accessed.…”
Section: Discussionsupporting
confidence: 90%
“…One group of authors reported that, of 131 cases of mediastinal lymph node sampling performed at the Johns Hopkins Hospital, 7 (5.3%) had samples that were considered inappropriate. (9) In the present study, the rate of inappropriate samples was 25%, which is similar to the rates reported in the literature for initial experiences. Contributing to that is the fact that the biopsies involved hilar lymph node stations, which had a higher rate of "inappropriate" samples when compared with the biopsies involving the subcarinal station, which is more easily accessed.…”
Section: Discussionsupporting
confidence: 90%
“…In a retrospective study by Feller-Kopman et al, the sensitivity, specificity, positive and negative predictive values (NPV) of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) cytology specimens from lymph nodes and lung tissue were 85.0%, 100%, 100% and 89.7%, respectively, when compared to histology. Concordant cytological and histological diagnoses were found in 64/88 (72.7%) cases, across all subtypes [31]. Sun et al reported similar results, with sensitivity, specificity, PPV and NPV of 88.9%, 96.4%, 97% and 87.1%, respectively, when EBUS-TBNA specimens of lymph nodes and peribronchial lung lesions were compared to tissue histology.…”
Section: Discussionsupporting
confidence: 74%
“…Novel diagnostic techniques are now available, providing relatively high accuracy rates [31,32]. In a retrospective study by Feller-Kopman et al, the sensitivity, specificity, positive and negative predictive values (NPV) of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) cytology specimens from lymph nodes and lung tissue were 85.0%, 100%, 100% and 89.7%, respectively, when compared to histology.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, transthoracic and/or transbronchial fine needle aspiration biopsy of the tumor become important approaches to obtain tumor tissue for diagnosis, staging and subclassification as well as for molecular characterization [6]. Due to the heterogeneity of lung cancer, accurate diagnosis on small biopsies can be challenging [2,3].…”
Section: Current Guidelines In the Subclassification Of Lung Cancermentioning
confidence: 99%